2013
DOI: 10.9755/ejfa.v25i8.16093
|View full text |Cite
|
Sign up to set email alerts
|

Market sustainability analysis of jenny milk cosmetics

Abstract: A quantitative market analysis was carried out to deepen the knowledge on some qualitative and quantitative aspects of jenny milk and cosmetics and, successively, a survey was carried out to study the influence of packaging on consumer liking. The first analysis was conducted using the quantitative method by interviews with a one to one questionnaire, consisting of 18 questions. In the second survey were interviewed 300 people with a questionnaire divided into two perception areas: of packaging paper, and of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…The milk origin is natural and it is a key ingredients widely used in the cosmetic industry. Various scientifi c studies have proven that the cosmetic products containing donkey milk showed exceptional high benefi ts for the skin [32]. The donkey milk is enrich in protein, minerals, essential fats, bioactive enzymes and various growth factors like ribofl avin, vitamin D etc.…”
Section: Cosmetics With Donkey Milkmentioning
confidence: 99%
See 1 more Smart Citation
“…The milk origin is natural and it is a key ingredients widely used in the cosmetic industry. Various scientifi c studies have proven that the cosmetic products containing donkey milk showed exceptional high benefi ts for the skin [32]. The donkey milk is enrich in protein, minerals, essential fats, bioactive enzymes and various growth factors like ribofl avin, vitamin D etc.…”
Section: Cosmetics With Donkey Milkmentioning
confidence: 99%
“…It is widely available as freeze dried powdered form and an ingredient in some European-imported chocolate bars. In Italy donkey milk is key component in some infant and medical nutrceuticals [5]. On the other hand there is not any real disadvantage of this incredible gift of nature.…”
Section: Introductionmentioning
confidence: 99%
“…Cow milk preparations (face and body creams, cleansing milk and tonic) are the most known by consumers. However, there are cosmetics made from other ruminants like camel (Kalejman 2011), sheep (Drader 2005) and goat (Ribeiro and Ribeiro 2010) or from monogastric species like horse and donkey (Medhammar et al 2012;Song 2012;Cosentino et al 2013a). Mare's milk is considered as an ingredient in Mongolian cosmetics because of its high content of polyunsaturated fatty acids, which make it readily absorbed by human skin (Temuujin et al 2006).…”
Section: Cosmetics Made With Jenny Milkmentioning
confidence: 99%
“…Some historical texts, such as the De Materia Medica of Dioscoride and the Naturalis Historia of Pliny the Elder, describing various uses of milk in cosmetics, and Ovid also, in his Medicamina Faciei Femineae, suggest beauty masks made with donkey milk (Virgili 1989). However, there are cosmetics made from other ruminants like camel (Kalejman 2011), sheep (Drader 2005) and goat or from monogastric species like horse and donkey (Medhammar et al 2012;Song 2012;Cosentino et al 2013a). Cow milk preparations (face and body creams, cleansing milk and tonic) are the most known by consumers.…”
Section: Cosmetics Made With Jenny Milkmentioning
confidence: 99%
“…More recently, Cosentino et al (2013a), in a study on the acceptability of different types of packaging for exalting the quality of cosmetics with jenny milk, found that consumers preferred the one evoking the concept of natural. A total of 300 consumers, aged in mean 33 years, evaluated the preferences by using a scale of values from 1 to 5.…”
Section: Cosmetics Made With Jenny Milkmentioning
confidence: 99%